Running Wild - Michael Morpurgo (India HarperCollins, 2009)
When 10-year-old Will's father dies in the Iraq war, his mother surprises him with a trip to Indonesia. But little could she have known what awaited them both there. The first Will knows that anything is wrong is when Oona, the elephant he is riding along the beach, begins to spook. Then, suddenly, she takes off into the jungle with Will on her back. And that's when Will sees the wave come crashing in! With his mother almost certainly drowned, with nothing to cling onto but an elephant and nothing to help him but the clothes on his back, Will faces a terrifying future. But maybe the jungle, and Oona the elephant, can help him - container.
Keywords: Mystery -- Mystery; Adventure -- Adventure